study on the effectiveness of direct current video (e-DC) improving learning outcomes of students and motivation towards learning Physics - Nurazlin Ahmad; Fatin Amirah Ahmad Shukri; Azuraida Amat; Nur Azalia Ahmad; Syarifah Norsuhaila Syed Mahmud (Pejabat Karang Mengarang UPSI, 2023)
COVID-19 is seen as a transformational agent for the widespread implementation of online learning at the school and higher education levels. A conducive learning environment, with the help of digital technologies, is essential to be incorporated into our learning process to enhance student's understanding of each course taken. The topic of Direct Current, in electricity, for foundation and matriculation level, is quite dense with formulas of electric current, resistance, and resistivity including the analysis of a simple Direct Current circuit. Therefore, we proposed the video of interactive notes (e-DC) which aims to improve students' understanding of the topic of Direct Current (DC). The notes created contains terminologies, formula, and a brief description of electric parameters such as electric current, resistivity, and conductivity. The current study was carried out among 183 pre-university students to highlight the effectiveness of the e-DC. To achieve the objective of the study, two pre-university centres namely the Centre for Defence Foundation Studies, UPNM, and Kolej Matrikulasi Pahang (KMPh) were selected through convenient sampling. The null hypothesis was that there would be no difference in the achievement between the students' scores using e-DC. The pretest-posttest comparison was used to test the effectiveness of the e-DC. The result indicated more improvement between their pre-test and post-test data causing the null hypothesis to be rejected. The findings of the study also found that most students (96%) stated their agreement that the learning process becoming more engaging and fun with the use of e-DC and students are motivated in learning Physics.